How emotional are emoji?: Exploring the effect of emotional valence on the processing of emoji stimuli. (March 2021) - Kaye, Linda K.; Rodriguez-Cuadrado, Sara; Malone, Stephanie A.; Wall, Helen J.; Gaunt, Elizabeth; Mulvey, Ashleigh L.; Graham, Charlotte
Abstract: Emoji are vastly becoming an integral part of everyday communication, yet little is understood about the extent to which these are processed emotionally. Previous research shows that there is a processing advantage for emotionally-valenced words over neutral ones, therefore if emoji are indeed emotional, one could expect an equivalent processing advantage. In the Pilot Study, participants ( N = 44) completed a lexical decision task to explore accuracy and response latency of word, face and emoji stimuli. This stimuli varied in emotional valence (positive vs. neutral). Main effects were found for stimuli type and valence on both accuracy and latency, although the interaction for accuracy was not significant. That is, there were processing advantages of positively-valenced stimuli over neutral ones, across all stimuli types. Also, faces and emoji were processed significantly more quickly than words, and latencies between face and emoji stimuli, irrespective of valence were largely equivalent. The Main Study recruited 33 participants to undertake a modified and extended version of the lexical decision task, which included three valence conditions (positive, negative and neutral) per stimuli type. Although no main effects were found for accuracy, there was a significant main effect found for stimuli but not for valence on latency. Namely, that word stimuli irrespective of valence were processed significantly more slowly than face or emoji stimuli. There was not a significant interaction between stimuli and valence, however. Therefore, overall although there was partial support for a processing advantage of emoji stimuli, this was not replicated across the studies reported here, suggesting additional work may be needed to corroborate further evidence. Highlights: Some evidence of a processing advantage of positively-valenced stimuli over neutral ones. Emoji may be processed emotionally to some extent. Emoji may be processed in an equivalent way as face stimuli.